Model Kepemimpinan Adaptif di Era Digital: Tinjauan Sistematis terhadap Strategi Kepala Sekolah dalam Menghadapi Perubahan - Inke Safitri; Ayu Sri Wahyuni; Indah Permatasari; Shobar Mualimin; Desi Suzara (Journal of Innovation in Teaching and Instructional Media, 2025)
The rapid development of technology in the digital era demands fundamental transformations in the management of educational institutions. In this context, principals have a strategic role as leaders who must be able to respond adaptively to the dynamics of change. This study aims to identify and analyze adaptive leadership models through a systematic review of various strategies implemented by principals in facing challenges and opportunities in the digital era. This study examines a variety of empirical and conceptual literature published in the last five years to synthesize best practices in adaptive leadership relevant to technological developments, shifting pedagogical paradigms, and the dynamics of modern school management. The review results indicate that effective adaptive leadership strategies focus on pedagogical technology integration, continuous human resource capacity development, flexibility in change management, and the creation of an innovative and collaborative school culture. These findings are expected to serve as a strategic reference for principals in designing policies and concrete steps to navigate the complexities of educational change in the digital era.